Energy Consumption Evaluation of Cellular Narrowband Internet of Things (NB-IoT) Modules - Elhaddad, Ahmed; Bruckmeyer, Heiko; Hertlein, Markus; Fischer, Georg (2020 IEEE 6th World Forum on Internet of Things (WF-IoT), 2020)
Communications field is witnessing an abrupt growth in the number of connected devices. The connected devices do not only include smartphones, but also connected devices through Internet of Things (IoT). Therefore, 3GPP defined Narrowband Internet of Things (NB-IoT) standard in LTE Rel-13 in order to serve low data rate IoT applications over mobile networks. NB-IoT modules are expected to have a low energy consumption in order to allow for battery usage of more than 10 years and provide a wide coverage area. At our institute, we developed a lab system setup in order to characterize the energy consumption of 3 NB-IoT modules from 3 different manufacturers using an LTE network mockup model. Accordingly, we measured the energy consumption by the modules during different phases of communication, and derived a data traffic dependent energy consumption model in order to estimate the corresponding expected battery lifetime. Furthermore, we measured the energy consumption per bit of the modules against the different number of uplink Narrowband Physical Uplink Shared Channel (NPUSCH) repetitions.
unpublished
Keywords: 5G; mMTC; LPWAN; CIoT; NB-IoT; Energy consumption; Battery lifetime

Time Synchronization of Spatial Separated Areas for AV-Production - Bruckmeyer, Heiko; Bühlmeyer, Jonas; Ackermann, Thomas; Fischer, Georg (2021 Joint Conference of the European Frequency and Time Forum and IEEE International Frequency Control Symposium (EFTF/IFCS), 2021)